A new East Asia toward a regional community - Mōri, Kazuko; Hirano, Kenʼichirō 1937- (NUS Press, 2007)
East Asia is normally identified as a group of countries lying along the western edge of the Pacific Ocean, but scholars have begun thinking about a East Asia that is a community rather than a set of sovereign states. This book looks at East Asia from a Northeast Asian perspective.